2023
DOI: 10.1039/d2se01796b
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-assisted low-temperature catalytic lignin-first depolymerization of pine wood biomass to selectively produce propyl guaiacol

Abstract: Lignin-first depolymerization of biomass using reductive catalytic fractionation (RCF) to valorize lignin while impeding the loss of the carbohydrate fraction in it is a potential resource recovery strategy for the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…The results showed that ultrasound acoustic cavitation could enhance the depolymerization of lignin, thus greatly enhancing the production of liquid fuels (Du et al 2020). Prabhudesai et al employed an ultrasonic pretreatment of the pine wood and the degree of delignification and the selectivity enhanced towards lignin monomers significantly (Prabhudesai et al 2023). Olguin-Maciel et al did a study on ultrasound pretreatment of non-conventional starch at different sonication temperature conditions (45, 70, and 90 °C).…”
Section: Effect Of Ultrasonic Pretreatmentmentioning
confidence: 99%
“…The results showed that ultrasound acoustic cavitation could enhance the depolymerization of lignin, thus greatly enhancing the production of liquid fuels (Du et al 2020). Prabhudesai et al employed an ultrasonic pretreatment of the pine wood and the degree of delignification and the selectivity enhanced towards lignin monomers significantly (Prabhudesai et al 2023). Olguin-Maciel et al did a study on ultrasound pretreatment of non-conventional starch at different sonication temperature conditions (45, 70, and 90 °C).…”
Section: Effect Of Ultrasonic Pretreatmentmentioning
confidence: 99%